The influence of parental educational expectations on primary school students’ social-emotional competence: the chain mediation effect of peer relationships and academic self-efficacy - Yang, Lianghong; Chen, Kaizhou; Ma, Suling; Lei, Yan (Frontiers in Psychology, 2025)
PurposeIn the context of deepening educational reform and emphasizing comprehensive development, social-emotional competence is crucial to the growth of primary school students. Parental educational expectations are a core element of the family micro-system, but their influence mechanism has yet to be explored in depth. Based on the ecosystem theory, this study examines the influence of parental educational expectations on primary school students’ social-emotional competence, as well as the chain mediation effect of peer relationships and academic self-efficacy.MethodsA questionnaire survey was conducted on 1,653 primary school students in grades 3–5 in Zhejiang Province using an adapted parental educational expectations questionnaire, a primary school students’ social-emotional competence questionnaire, a peer relationships questionnaire, and an academic self-efficacy questionnaire. AMOS 28.0 was used to construct and test a chain mediation effect model.ResultsThe analysis found that parental educational expectations could directly and positively predict primary school students’ social-emotional competence (β = 0.22, p = 0.001, accounting for 28.0%); peer relationships partially mediated the relationship between parental educational expectations and social-emotional competence (β = 0.26, p < 0.001, accounting for 34.0%); academic self-efficacy partially mediates the relationship between parental educational expectations and social-emotional competence (β = 0.19, p < 0.001, accounting for 24.1%); parental educational expectations indirectly affect social-emotional competence through the chain mediation effect of “peer relationships → academic self-efficacy” (β = 0.11, p < 0.001, accounting for 13.9%).ConclusionParental educational expectations not only directly promote primary school students’ social-emotional competence, but also have an indirect influence through peer relationships, the independent mediating effect of academic self-efficacy, and the chain mediation effect of the two. This study reveals the mechanism of the synergistic effects of family, peers, and individual psychological resources, providing inspiration for educational practice.